Morality as a Basic Psychological Need. Issue 4 (May 2019) - Prentice, Mike; Jayawickreme, Eranda; Hawkins, Ashley; Hartley, Anna; Furr, R. Michael; Fleeson, William
We investigate the long-standing yet understudied assumption that feeling moral is a basic psychological need, perhaps like the needs to feel autonomous, competent, and related (ACR). We report an empirical "entrance exam" on whether morality should be considered a need. Specifically, we applied to morality a pioneering method from which Sheldon and colleagues provided evidence that ACR are basic psychological needs. In two studies and four samples, participants recalled events in which they felt un/satisfied, meaningful, pleasurable, at their best, and at their worst. They rated how much candidate psychological needs were satisfied during them. Morality was frequently as or more satisfied than ACR during peak events. Further, it was positively related to indices of positive functioning. These findings suggest feelings of being moral may help people identify times when life is going well. Further, they suggest that morality may be a fundamental psychological need and warrants further investigation.